2021
DOI: 10.1111/micc.12678
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of brain microvasculature and blood flow in vivo: Feasibility study using confocal laser endomicroscopy

Abstract: Intraoperative visualization of blood flow characteristics is of keen interest during many neurosurgical procedures. Development of cerebral videoangiography with fluorescein sodium 1 and indocyanine green (ICG) 2,3 as contrast agents has provided extraordinarily useful intraoperative methods for neurosurgeons to rapidly assess blood flow in cerebral vessels. Although wide-field fluorescence imaging techniques with fluorescein and ICG are used extensively, their main drawbacks are the short temporal imaging re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Belykh and colleagues investigated the feasibility of CLE to qualitatively and quantitatively analyze real-time blood flow patterns in brain under normal conditions, after injury and in pathologic brain and spinal cord microvasculature in a large animal model and patient samples ( 27 ). In the swine model, SF concentrations ranged from 1 - 5 mg/kg and 0.1% - 0.005%/5 ml.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Belykh and colleagues investigated the feasibility of CLE to qualitatively and quantitatively analyze real-time blood flow patterns in brain under normal conditions, after injury and in pathologic brain and spinal cord microvasculature in a large animal model and patient samples ( 27 ). In the swine model, SF concentrations ranged from 1 - 5 mg/kg and 0.1% - 0.005%/5 ml.…”
Section: Resultsmentioning
confidence: 99%
“…Looking at the only available CONVIVO vascular experience by Belykh and colleagues from 2021, patients received 5 ml of 10% SF i.v. 5 minutes prior to CLE imaging ( 27 ). The earliest visualization of the vessel wall was 8 minutes after SF injection, with visualization being more common at approximately 30 minutes after injection.…”
Section: Discussionmentioning
confidence: 99%
“…Belykh et al examined the presence of thrombosis, flow velocity changes, and agglutination in gliomas during neurosurgery, demonstrating the feasibility and potential of examining capillaries by CLE. It was demonstrated that lymphatic channels could also be differentiated from blood vessels [23]. Further research is needed to evaluate the transferability of these results in the head and neck region.…”
Section: Discussionmentioning
confidence: 98%
“…Future analysis will include an assessment of tumor microvasculature in addition to tumor cell morphology and architecture. Interpretation of erythrocyte flow, thrombosis, and velocity changes may help to classify glioma subtypes, normal and injured brain tissues (33). Due to the lack of blood flow in ex vivo samples, these features were not included during the CNN training process in this study.…”
Section: Discussionmentioning
confidence: 99%